A disorder-sensitive emergent vortex phase identified in high-Tc superconductor (Li, Fe)OHFeSe. (1st June 2022) - Li, Dong; Shen, Peipei; Tian, Jinpeng; He, Ge; Ni, Shunli; Wang, Zhaosheng; Xi, Chuanying; Pi, Li; Zhang, Hua; Yuan, Jie; Jin, Kui; Talantsev, Evgeny F; et al.
Abstract: The magneto-transport properties are systematically measured under c -direction fields up to 33 T for a series of single-crystal films of intercalated iron-selenide superconductor (Li, Fe)OHFeSe. The film samples with varying degree of disorder are grown hydrothermally. We observe a magnetic-field-enhanced shoulder-like feature in the mixed state of the high- T c (Li, Fe)OHFeSe films with weak disorder, while the feature fades away in the films with enhanced disorder. The irreversibility field is significantly suppressed to lower temperatures with the appearance of the shoulder feature. Based on the experiment and model analysis, we establish a new vortex-phase diagram for the weakly-disordered high- T c (Li, Fe)OHFeSe, which features an emergent dissipative vortex phase intermediate between the common vortex glass and liquid phases. The reason for the emergence of this intermediate vortex state is further discussed based on related experiments and models.